Finding out good Osaekomi moves and developing evaluation critcria for OIsaekomi techniques - Yabune, T.; Nakajima, H.; Ariyama, A.; Fujino, T. (Association for the Scientific Studies on Judo, Kodokan, 2017)
In order to find out the trick to osaekomi techniques for judo, we conducted a study in which 32 people with judo experience varying in skill levels and level o f competition held a judo master in an osaekomi. The moves were observed and assessed by four judo masters. Based on their assessments, it became clear that the judo masters who were able to escape the osaekomis were able to move their shoulders freely while being held down. We therefore came to the conclusion that a good osaekomi is one in which the opponent, is held down in a way that. prevents them him/her moving his/her shoulders freely. Furthermore, in order to study the trick to preventing the opponent, from moving his/her shoulders freely, we conducted a study which involved holding down two judo masters in an osaekomi. Based on the results of the study, we came to the conclusion that. the trick shared by good osaekomis is that. the holder keeps his/her upper arms to the body and presses his/her chest against. their opponent, to hold his/her shoulders down, and stabilizes his/her lower body by lowering the hips.In addition, we developed evaluation criteria based on the trick to performing osaekomi moves and created a point system for the 60 osaekomi techniques for evaluating students` skills based on the criteria. After analyzing a correlation between the point system and the duration of the osaekomi, we found that there is a strong correlation between the two. This correlation verified that the evaluation criteria for osaekomi are appropriate.